Numerical modelling of a stoker furnace operated under indirect co-firing of biomass - Litka Rafał; Kalisz Sylwester (Chemical and Process Engineering)
The subject of the CFD analysis presented in this paper is the process of biomass indirect co-firing carried out in a system composed of a stoker-fired furnace coupled with a gasification reactor. The installation is characterised by its compact structure, which makes it possible to minimise heat losses to the environment and enhance the physical enthalpy of the oxidising agent – flue gases – having a favourable chemical composition with oxygen and water vapour. The test results provided tools for modelling of biomass thermal processing using a non-standard oxidiser in the form of flue gases. The obtained models were used to optimise the indirect co-combustion process to reduce emissions. An overall effect of co-combustion of gas from biomass gasification in the stoker furnace is the substantial reduction in NO emissions by about 22%.